Oregon Writes Open Writing Text - Kepka, Jenn (Open textbook library., 2018)
This textbook guides students through rhetorical and assignment analysis, the writing process, researching, citing, rhetorical modes, and critical reading. Using accessible but rigorous readings by professionals throughout the college composition field, the Oregon Writes Writing Textbook aligns directly to the statewide writing outcomes for English Composition courses in Oregon.